'Would you like to meet a ghost?': Repetition and spectral posthumanism in Kiyoshi Kurosawa's Kairo. Issue 2 (1st October 2018) - Lovasz, Adam
Kiyoshi Kurosawa's 2001 film, Kairo (Pulse), is an enigmatic piece of cinema. Even its genre cannot be neatly delineated. Part horror film, part art-house cinema, part social commentary, Kairo has a quality all of its own. While some commentators have identified the particular style of directing peculiar to the 'other' Kurosawa, even finding this mode of directing to be compatible with auteur modes of filmmaking, I seek to capture the singularity of the film's content. In spite of the fact that Kurosawa as a director is notably repetitious in his choice of themes, the circumstance of repetition, as Gilles Deleuze reminds us in his 1969 book, Difference and Repetition, does not preclude the singular, evental nature of any and all such repetitions. Here I understand the phrase 'repetition' in the Deleuzian sense of the term, denoting a pure 'difference without a concept'. Repetition is difference as it actualizes itself in the world. According to the Deleuzian view, underneath laws and generalities there may be found countless layers of singularities, processes and becomings that cannot be easily accessed. Obscurity, as I hope to show through numerous examples from Kairo's screenplay, seems to be a pervasive phenomenon in Kurosawa's apocalyptic vision of cybernetic society. Instead of connecting human beings with one another, information and communication technologies come to serve as conduits for spectral presences that produce new forms of disappearance. Productivity, far from being opposed to absence, is transformed during the course of the film into the virally proliferating production of nothing. For Deleuze, signs become deadly when they strike 'with full force'. When the absolutely other strikes into the very heart of our Being, our very existence is endangered by machineries of abyssal replication. Every single character in Kairo is alienated from themselves and one another. The only vital, functioning form of community is, perversely, the realm of the dead, mediated by the transgressive power of cybernetic networks. As Valerie Wee has pointed out, the sense of lost community and the decline of tradition seems to be a salient theme of Kurosawa's Kairo, as opposed to its rather more shallow 2006 American remake. Registering the circumstance of cultural decline and societal extinction, a very real phenomenon in early twenty-first-century Japan, should not be equated, however, with some form of nostalgic pining for a bygone era. Rather, I propose that we view Kairo as a deeply philosophical meditation on the posthuman condition, and the immanent possibilities of haunting repetitions lying beyond representation.